PERANCANGAN SISTEM INFORMASI AKUNTANSI DENGAN METODE DECISION SUPPORT SYSTEM (DSS) - Dony Waluya Firdaus; Lina Rosalina; Hery Dwi Yulianto (Labkat Press KA FTIK UNIKOM, 2012)
The research was conducted at PT. Sinkona Indonesia Lestari is a manufacturing company engaged in the industry that produces quinine salt of quinine and its derivatives. The Company requires cash flow of financial statements information that is fast, precise, accurate and up to date for management decision making. Authors are interested with the title